Post-exercise ingestion of low or high molecular weight glucose polymer solution does not improve cycle performance in female athletes - Mock, M. G.; Hirsch, K. R.; Blue, M. N.; Trexler, E. T.; Roelofs, E. J.; Smith-Ryan, A. E. (The Journal of Strength and Conditioning Research, 2021)
The current study sought to evaluate the effects of postexercise ingestion of a high molecular weight (HMW) glucose polymer solution compared with an isocaloric low molecular weight (LMW) solution or placebo (PLA) on subsequent cycling performance in female athletes. In a randomized, double-blind, placebo-controlled, cross-over design, 10 competitive female cyclists (Mean ± SD; Age = 25.7 ± 5.0 years; Vo2peak = 49.7 ± 4.3 ml/kg/min) completed 3 testing sessions separated by 7-10 days. Visits consisted of a ride-to-exhaustion (RTE) at 75% Vo2peak, followed by immediate consumption of 700 ml containing either: 1.2 g/kg LMW (maltodextrin/dextrose/fructose); 1.2 g/kg HMW (Vitargo); or 0.066 g/kg PLA (noncaloric flavoring). After 2 hours of rest, subjects performed a 15-minute time trial (TT). Respiratory exchange ratio (RER) was assessed via indirect calorimetry during exercise. Total body water (TBW) was measured using bioelectrical impedance to assess fluid balance. When covaried for estrogen, there was no treatment effect on distance (km; p = 0.632) or power output (watts; p = 0.974) during the 15-minute TT. Respiratory exchange ratio was not significantly different during the LMW and HWM TTs (p > 0.999), but both were significantly higher than PLA (p = 0.039, p = 0.001, respectively). Changes in total body water pre-exercise to postexercise were not significantly different between trials (p = 0.777). Despite benefits of HMW on cycling performance previously reported in males, current results demonstrate no ergogenic effect of HMW or LMW in females. Sex differences in substrate utilization may account for the discrepancy, and further research involving performance nutrition for female athletes is merited.